Réponses

2014-01-09T12:30:48+01:00
1.
A = 9x² + 6x + 1 + 4x² -28x + 49 = 13x² - 22x + 50 
B = 4/9x² - 16/15x + 16/25
C = 4x² - 49 - x² + 4x - 4 = 3x² + 4x - 53
2.
D = x(5x-2)
E = (3x - 1)² 
F = (x-7)(x+1 - 5) = (x-7)(x-4)
G = (2x-3)(2x+3)
3.
1. H = 18x² + 6x - 27x - 9 - 4x² + 12x - 9 = 14x² - 9x - 18
2.H(-2) = -5x-21 - 49 = -105 - 49 = 56
   H(3/2) = 3(3-3)(21/2 + 6) = 0
3. 6x - 9 = 3(2x - 3) 
H = 3(2x-3)(3x+1) - (2x-3)² = (2x-3)(9x + 3 - 2x + 3) = 3(2x-3)(7x+6)
4.  3(2x-3)(7x+6) = 0 => x = 3/2 ou x = -6/7
ex4.
1. A1 = (2x+1)(3x-9) 
2. A2 = (3x-7)² - 4
3. A1 - A2 = 6x² - 18x + 3x - 9 - 9x² + 42x - 49 - 4 = 0 => -3x² +27x - 62 = 0 
=> x² - 9x + 62/3 = 0 => x² - 9x + 81/4 + 5/12= 0  => (x - 9/2)² + 5/12 = 0 ce qui n'est pas possible